SCUBA-2 Ultra Deep Imaging EAO Survey (STUDIES). II. Structural properties and near-infrared morphologies of faint submillimeter galaxies - Chang, Y; Ferraro, N; Wang, W; Lim, C; Toba, Y; An, F; Chen, C; Smail, I; Shim, H; Ao, Y; Bunker, A; Conselice, C; et al. (IOP Publishing, 2018)
We present structural parameters and morphological properties of faint 450 μm selected submillimeter galaxies (SMGs) from the JCMT Large Program, STUDIES, in the COSMOS-CANDELS region. Their properties are compared to an 850 μm selected and a matched star-forming samples. We investigate stellar structures of 169 faint 450 μm sources (S 450 = 2.8-29.6 mJy; S/N > 4) at z < 3 using HST near-infrared observations. Based on our spectral energy distribution fitting, half of such faint SMGs (L IR = 1011.65±0.98 L o) lie above the star formation rate (SFR)/stellar mass plane. The size-mass relation shows that these SMGs are generally similar to less-luminous star-forming galaxies selected by NUV - r versus r - J colors. Because of the intrinsic luminosity of the sample, their rest-frame optical emission is less extended than the 850 μm sources (S 850 > 2 mJy) and more extended than the star-forming galaxies in the same redshift range. For the stellar mass and SFR-matched sample at z ≃ 1 and z ≃ 2, the size differences are marginal between faint SMGs and the matched galaxies. Moreover, faint SMGs have similar Sérsic indices and projected axis ratios as star-forming galaxies with the same stellar mass and SFR. Both SMGs and the matched galaxies show high fractions (∼70%) of disturbed features at z ≃ 2, and the fractions depend on the SFRs. These suggest that their star formation activity is related to galaxy merging and the stellar structures of SMGs are similar to those of star-forming galaxies. We show that the depths of submillimeter surveys are approaching the lower luminosity end of star-forming galaxies, allowing us to detect galaxies on the main sequence.